2011
DOI: 10.1172/jci57925
|View full text |Cite
|
Sign up to set email alerts
|

A uroguanylin-GUCY2C endocrine axis regulates feeding in mice

Abstract: Intestinal enteroendocrine cells are critical to central regulation of caloric consumption, since they activate hypothalamic circuits that decrease appetite and thereby restrict meal size by secreting hormones in response to nutrients in the gut. Although guanylyl cyclase and downstream cGMP are essential regulators of centrally regulated feeding behavior in invertebrates, the role of this primordial signaling mechanism in mammalian appetite regulation has eluded definition. In intestinal epithelial cells, gua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
275
4
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(293 citation statements)
references
References 55 publications
13
275
4
1
Order By: Relevance
“…In mice, pro-UGN is released from the gut immediately after nutrient intake and is converted into active UGN within the hypothalamus, thereby activating GUCY2C and reducing food intake (11). In agreement with these results, pharmacological stimulation of GUCY2C inhibited feeding in obese mice, and mice lacking GUCY2C are hyperphagic and more prone to develop metabolic syndrome (11).…”
supporting
confidence: 52%
See 2 more Smart Citations
“…In mice, pro-UGN is released from the gut immediately after nutrient intake and is converted into active UGN within the hypothalamus, thereby activating GUCY2C and reducing food intake (11). In agreement with these results, pharmacological stimulation of GUCY2C inhibited feeding in obese mice, and mice lacking GUCY2C are hyperphagic and more prone to develop metabolic syndrome (11).…”
supporting
confidence: 52%
“…Whereas one report (11) showed a decreased food intake 2 h after the central injection of STs, a subsequent study (12) failed to detect changes in food intake after the administration of ST or UGN. Similar to the first report (11), we found that UGN (25 mg i.c.v.)…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…An endocrine axis regulating feeding in mice was recently described for UGN that could have clinical implications for the control of appetite, obesity and metabolic syndrome (Valentino et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, uroguanylin participates in an endocrine axis regulating feeding in mice (Valentino et al, 2011). In this system, prouroguanylin is converted to uroguanylin in the central nervous system , activates guanylyl cyclase 2C (GUCY2C) receptors in the brain to reduce food intake in mice.…”
Section: Introductionmentioning
confidence: 99%